Injuries among disabled athletes during the 2002 Winter Paralympic Games - Webborn, N.; Willick, S.; Reeser, J. C. (Medicine & Science in Sports & Exercise, 2006)
Purpose: This prospective injury surveillance study was conducted to better understand the types of and risk factors of injuries sustained by athletes with disabilities competing in adapted winter sports at the elite level.